Pulvinar Sign, Stroke and Their Relationship with Fabry Disease: A Systematic Review and Metanalysis - Juan Fernando Ortíz; María Belén Solís; Syed Saad Ali; Mahika Khurana; Juan Andrés Moncayo; Nishel Yogesh Kothari; Mateo Alzamora; Ahmed Eissa-Garces; Ghanshyam Patel; Gustavo Andrés Monteros; Meghdeep Sen; Jonathan Quiñonez (MDPI AG, 2022)
Background: Fabry disease (FD) is the second most common lysosomal storage disorder. This disorder affects multiple systems that include the cardiac, renal, and nervous system. The pulvinar sign (PS) is a relatively common sign seen in patients with FD. The PS is a bilateral, symmetrical pulvinar high signal relative to the signal intensity seen on unenhanced T1-weighted brain MR imaging. Methods: We conducted a systematic review with metanalysis to analyze the pool prevalence of the disorder. We used the Moose Guidelines and PRISMA Protocol for this systematic review and Robins 1 to access the BIAS of the study. To analyze the pool prevalence, we used "Open Meta-Analysis" software for analyzing the study. We used "Review Manager 5.4" to analyze the odds ratio between patients with and without the PS and patients with and without stroke among patients with FD. Results: We gather 12 studies from 2003 to 2021 for the analysis of this study. The pool prevalence of the study was 0.146 (0.076-0.217) (62/385 cases) with a 95% CI (0.0945-0.415) (p < 0.01). The prevalence was much higher in men (59 cases) than in women (3 cases). There was no relationship between the pulvinar sign and patients with stroke among patients with Fabry disease. Odds ratio 1.97 95% CI (0.35-11.21), p = 0.44; Tau2 = 0.77. There seems to be a correlation with renal failure (RF), but there were very few studies to conduct a metanalysis with RF. Conclusions: The prevalence of the PS among all studies was 23.9%; the prevalence of this sign is higher among males. We found that FD patients who had strokes did not have higher odds of presenting with the Pulvinar Sign than the FD patients who did not suffer a stroke. Patients with renal failure and FD seem to have a higher tendency to have the PS, but there were not enough studies to analyze that theory. Overall, we think the pulvinar sign has a poor prognostic value in patients with Fabry's disease.